Lead engagement partner workload, partner-client tenure and audit reporting lag - Wan Hussin, Wan Nordin; Bamahros, Hasan Mohammed; Shukeri, Siti Norwahida (Emerald Publishing Limited, 2018)
Purpose – Motivated by a recent call from DeFond and Zhang (2014) for auditing scholars to use “a richer set of audit firm, auditor office, and individual auditor characteristics to capture competency”, this study aims to extend the related line of research by examining the association between lead engagement partner workload, defined as the number of public listed clients the partner is in charge of, and audit lag.The moderating effects of partner tenure on the partner workload–audit lag relationship have also been examined. Design/methodology/approach – The association between auditor workload and financial reporting timeliness on 651 non-financial firms listed on Bursa Malaysia is tested in this study.Data to compute the partner workload are based on 222 lead engagement partners who signed off the audit reports for all 892 public listed firms in 2013. Findings – The busy auditors are observed to prolong audit lags, and the effect is more acute for non-Big 4 clients, busy season clients and a short partner tenure.The engagement partners with heavy workload can also mitigate the adverse effects of reduced audit report timeliness when they have a longer partner–client tenure.Research limitations/implications – This study may understate the level of engagement partner workload when partners have private firms in their client portfolios. Notwithstanding that, this study reiterates the growing importance of examining accounting and auditing outcomes at the individual partner level.Practical implications – The findings that over-burdened engagement partner takes a longer time to complete the audit add to the current debate, where audit regulators and various stakeholders are actively promoting discussions on potential indicators of audit efficiency and quality.Originality/value This study provides new evidence on the association between partner workload and audit reporting lag, which has hitherto been unexplored. This study also extends the research carried out by Gul et al. (2017) and Sharma et al. (2017) by providing additional evidence on the relationship between partner tenure and audit delay.